DESAIN DAN SIMULASI SOCKET PROSTESIS BAWAH LUTUT DENGAN VARIASI MATERIAL BERBASIS KOMPOSIT - Luthfi Ali Masykur; Donny Suryawan (P3M Politeknik Negeri Indramayu, 2021)
Each year, the number of disabled people in Indonesia increases. About 2.4 million people had some trouble walking in 2014. It includes 650,000 individuals who have significant difficulty walking and ascending stairs. Lower limb prostheses are an option for those who are unable to walk due to leg amputation. One of the most necessary parts of the below-knee prosthesis is the socket. Almost the local prosthetics socket did not give adequate information about the specification. It is a weakness of the local product because there is no guarantee of product safety. The lack of references and standards makes it difficult for manufacturers to improve their products to compete with imported products. This research is focused on the design and simulation of prosthesis sockets with various composite-based materials. The simulation method was adapted from ISO 10328 standard as the testing standard for prosthetics foot. The result shows that the sockets can be used for Indonesians with a calf circumference between 317-345 mm. The simulation results show that the suitable material for use is carbon fiber composite material with a thickness of 3 mm with a bolt hole of 6 mm.